61‐1: Invited Paper: OLED Technology for Automotive Display Applications. Issue 1 (28th June 2022) - Tarnowski, Tomasz; Kreuzer, Markus; Haidenthaler, Robert; Aichholz, Markus; Pohl, Matthias; Pross, Achim
Abstract : The automotive market becomes one of the most interesting application areas for OLED display technology, creating modern and very exciting environment. Many believe that the use of OLED technology can revolutionize the premium automotive display sector, offering a variety of new properties such as flexible integration or superior image quality that would not be possible with other enabling display technologies. However, the harsh environmental conditions of automotive display applications shall be considered in order to satisfy the lifetime of the product and overall quality requirements. Furthermore, the final integration and use case shall be taken into account. We present a general guideline, testing criteria and application properties of an OLED display product, which allowed us to overcome the feasibility issues of OLED technology and successfully introduce it into Mercedes‐Benz passenger cars.